2016
DOI: 10.3390/ijms17071160
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Metabolism Disorder in Primary Chondrocytes from Adolescent Idiopathic Scoliosis Girls

Abstract: To investigate the underlying mechanisms of low metabolic activity of primary chondrocytes obtained from girls with adolescent idiopathic scoliosis (AIS); AIS is a spine-deforming disease that often occurs in girls. AIS is associated with a lower bone mass than that of healthy individuals and osteopenia. Leptin was shown to play an important role in bone growth. It can also regulate the function of chondrocytes. Changes in leptin and Ob-R levels in AIS patients have been reported in several studies. The underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
(33 reference statements)
0
26
0
2
Order By: Relevance
“…Then, the remaining 36 articles were read through, and 25 were unqualified due to inappropriate study or incomplete data for systematic review. Eventually, 9 studies were qualified for this meta-analysis [ 11 , 12 , 17 – 22 ]. QUADAS-2 quality assessment for the included studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the remaining 36 articles were read through, and 25 were unqualified due to inappropriate study or incomplete data for systematic review. Eventually, 9 studies were qualified for this meta-analysis [ 11 , 12 , 17 – 22 ]. QUADAS-2 quality assessment for the included studies is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The extracted information from each paper, including first author, year of publication, number of cases and controls, and mean levels of leptin and ghrelin, is shown in Table 1 . Among these included 9 articles, 6 articles explored changes of serum leptin and sOB-R in AIS [ 11 , 12 , 17 19 ], another 2 explored changes of ghrelin in AIS [ 21 , 22 ], while the remaining one study both leptin and ghrelin in AIS [ 20 ]. A total of 700 AIS patients and 3536 healthy controls were included for the meta-analysis of leptin, while 198 AIS patients and 138 healthy controls were included for ghrelin analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Leptin and ghrelin antagonize each other in regulating energy balance [ 14 ]. A number of studies have reported serum leptin and ghrelin level disorders in AIS patients [ 15 20 ]. However, the significance of leptin or ghrelin as a biomarker in progressive AIS patients has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It binds to the leptin receptor (Ob-R) which is expressed as several different isoforms 8 . Leptins and leptin receptors have now been shown to be expressed in a number of organs and tissues in addition to adipose tissue 9 , 10 . Leptins have diverse effects on bone tissue regulation with leptin receptor mutations 11 .…”
Section: Introductionmentioning
confidence: 99%